Operasi Plastik pada Wajah untuk Estetika Perspektif UU Kesehatan dan Yusuf Al-Qaradhawi - Azuratun Nasuha; Muhammad Iqbal Irham; Muhammad Faisal Hamdani (CV Rewang Rencang, 2025)
Facial plastic surgery for aesthetic purposes has become an increasingly prominent practice in modern medical procedures. While such interventions offer significant physical transformations also raise various ethical, medical, and legal questions particularly within the frameworks of law and contemporary Islamic jurisprudence. This study aims to analyze facial plastic surgery from two perspectives: Indonesia’s Health Law No. 17 of 2023 and the views of contemporary Islamic scholar Yusuf al-Qaradawi. Within the context of Health Law, plastic surgery is considered a legitimate medical practice as long as it adheres to principles of patient safety, medical ethics, and does not endanger an individual's health. The law emphasizes the importance of valid medical purposes in clinical practice and calls for strict oversight of aesthetic procedures to prevent exploitation and misuse. Meanwhile, according to Yusuf al-Qaradawi, cosmetic surgery for aesthetic enhancement may be deemed permissible as long as it does not contravene fundamental Islamic principles such as avoiding permanent changes that result in deception or violate the integrity of God's creation. This study employs a literature review method by examining relevant sources related to the Health Law and Yusuf al-Qaradawi's fatwas concerning aesthetics and bodily alteration in Islam. The findings reveal a tension between individual freedom to undergo cosmetic procedures and the obligation to uphold health and medical ethics within both positive law and contemporary fiqh. Overall, both perspectives advocate for a balanced approach to plastic surgery, prioritizing safety, well-being, and noble intentions.